Student Perception on Multimedia Implementation in Improving Speaking Skill in ELT - Wibisana, Mohammad Andre; Aditama, Madya Giri; Anasa, Firyal Afaf (PROJECT (Professional Journal of English Education), 2025)
Speaking is an important skill for oral communication in English. For Indonesian students learning English as a foreign language, speaking is a difficult skill to acquire because producing speech from a non-native language is more difficult than understanding it. One method to improve speaking skill, is to implement multimedia in presentation. The objectives of this study are (1) analyzing student’s speaking skill by implementing multimedia in presentation; and (2) investigating student’s perception on implementation of multimedia in presentation. It is a qualitative research with phenomenological approach. Data was collected from observation and interview. The participants of this study were 18 undergraduate students of Nursing study program in Universitas Muhammadiyah Kendal Batang. The results show that implementation of multimedia in presentation has improved student’s speaking skill and the students had positive perceptions on implementation of multimedia in presentation. This was supported by observation and interview results, where majority of the students were able to speak full English after six presentations were done and had positive statements on the implementation of multimedia in presentation.